2002
DOI: 10.1094/mpmi.2002.15.7.693
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Trehalase in Arabidopsis Plants Infected With the Trehalose-Producing Pathogen Plasmodiophora brassicae

Abstract: Various microorganisms produce the disaccharide trehalose during their symbiotic and pathogenic interactions with plants. Trehalose has strong effects on plant metabolism and growth; therefore, we became interested to study its possible role in the interaction of Arabidopsis thaliana with Plasmodiophora brassicae, the causal agent of clubroot disease. We found that trehalose accumulated strongly in the infected organs (i.e., the roots and hypocotyls) and, to a lesser extent, in the leaves and stems of infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
110
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 37 publications
11
110
0
Order By: Relevance
“…This sugar is thought to be synthesized by the pathogen, and then released to the host cell, because putative gene for trehalose-6-phosphate synthase, an enzyme on the pathway of trehalose synthesis was detected in the pathogen. This sugar passively disturbs the sugar metabolism of the host plant (Brodmann et al 2002).…”
Section: Hormonal Regulation and Metabolism Of Clubroot Formationmentioning
confidence: 99%
“…This sugar is thought to be synthesized by the pathogen, and then released to the host cell, because putative gene for trehalose-6-phosphate synthase, an enzyme on the pathway of trehalose synthesis was detected in the pathogen. This sugar passively disturbs the sugar metabolism of the host plant (Brodmann et al 2002).…”
Section: Hormonal Regulation and Metabolism Of Clubroot Formationmentioning
confidence: 99%
“…Transcriptional profiles and microarray data sets show that AtTRE1 expression is increased in vegetative tissues during senescence and is induced by auxin, cytokinin, sugar availability, and abiotic stresses such as drought (Müller et al, 2001b;Zimmermann et al, 2004;Brenner et al, 2005;Rolland et al, 2006). An important role for trehalase has been proposed during plant-microbe interactions in plants hosting trehalose-producing microorganisms, such as arbuscular mycorrhizal fungi, rhizobia, and the clubroot disease-inducing pathogen Plasmodiophora brassicae (Müller et al, 1994;Schubert and Wyss, 1995;Brodmann et al, 2002). Recently, an Attre1 knockout line was characterized (SALK_147073C; Alonso et al, 2003) and reported to have a 2-fold increase in T6P levels when grown on sorbitol (Delatte et al, 2011a).…”
mentioning
confidence: 99%
“…This gene codes for the enzyme trehalose-6-phosphate synthase involved in the synthesis of trehalose, a typical microbial sugar known to accumulate in a variety of symbiotic or pathogenic interactions of microorganisms with plants, as well as in response to salt stress (10,33). Trehalose-producing organisms could affect the carbon metabolism of infected plants by converting the products of photo- (32,34,54).…”
mentioning
confidence: 99%